2022
DOI: 10.1200/op.20.01055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Performance Status on Response and Survival Among Patients Receiving Checkpoint Inhibitors for Advanced Solid Tumors

Abstract: PURPOSE Clinical trials, which led to the approval of immune checkpoint inhibitors (ICI), have been almost exclusively performed in patients with good Eastern Cooperative Oncology Group performance status (ECOG PS of 0-1). However, ICI remains an attractive option for patients with advanced tumors and poor PS. We hypothesized that patients with ECOG PS ≥ 2 would have worse outcomes with ICI. METHODS We retrospectively identified patients with advanced solid tumors who were treated with ICI at our institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Patients with ECOG PS >1 are frequently excluded from pivotal randomized trials and outcomes in this group are therefore mainly based on retrospective studies from real world settings. Treatment with CPIs seems to be safe and effective also in patients with poor PS even though response rates and overall survival in this group is clearly inferior compared to patients with PS 0–1 16,31,32 . This observation is supported by our results indicating that PS as a single variable does not predict the development of IRAEs.…”
Section: Discussionsupporting
confidence: 78%
“…Patients with ECOG PS >1 are frequently excluded from pivotal randomized trials and outcomes in this group are therefore mainly based on retrospective studies from real world settings. Treatment with CPIs seems to be safe and effective also in patients with poor PS even though response rates and overall survival in this group is clearly inferior compared to patients with PS 0–1 16,31,32 . This observation is supported by our results indicating that PS as a single variable does not predict the development of IRAEs.…”
Section: Discussionsupporting
confidence: 78%
“…Multiple studies in bladder cancer have indicated that patients with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 2 have worse outcomes with ICI therapy than those with ECOG PS < 2 [34][35][36]. Prospective clinical trials with ECOG PS ≥ 2 are lacking, despite ICI therapy being an enticing option for the poor PS population.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in bladder cancer have indicated that patients with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 2 have worse outcomes with ICI therapy than those with ECOG PS < 2 (33)(34)(35). Prospective clinical trials with ECOG PS ≥ 2 are lacking, despite ICI therapy being an enticing option for the poor PS population.…”
Section: Discussionmentioning
confidence: 99%